Microstructural evolution and deformation mechanisms of Khao Kho Fault, Thailand. (July 2020) - Kanitpanyacharoen, Waruntorn; Chornkrathok, Sasithorn; Morley, Christopher K.; Wenk, Hans-Rudolf
Abstract: Lithologies and microstructures of fault rocks from the Khao Kho Fault in Thailand are investigated to understand fault behavior and underlying deformation mechanisms. Fault gouges in the shear zone are mainly composed of kaolinite, illite-mica, and illite-smectite and exhibit weak preferred orientation, ranging from 1.2 to 2.3 m.r.d. These fault cores are characterized by high localized strain and intense deformation due to cataclasis and frictional granular flow mechanisms, which produce transgranular fractures, rounded quartz grains, and an ultrafine clay matrix. In contrast, wall rocks show stronger clay preferred orientation, up to 3.9 m.r.d., despite having less clay content than the fault gouges. Much larger fault-related bent and sheared clay grains are present in the wall rocks, suggesting less severe deformation. The discrepancy between fault cores and wall rocks indicate that the development of fabrics is related to faulting and authigenic processes. Weak fabrics in the slip zone are attributed to the comminution of grains and neomineralization, allowing clay platelets to grow and rotate in many directions. In addition, the abundance of metal oxides indicates extensive, multiple fluid alteration processes, which further influence microstructures and fault properties. Highlights: Wall rocks show strong clay fabrics despite having less clay content than the fault gouges. Weak fabrics in the slip zone are attributed to the comminution of grains and neomineralization. Fault gouges show high localized strain and intense deformation due to cataclasis and frictional granular flow mechanisms. Kaolinite is the most abundant mineral in fault gouges while illite-group is the most dominant clay in wall rocks.